2011
DOI: 10.1371/journal.pone.0022387
|View full text |Cite
|
Sign up to set email alerts
|

ISL1 Promotes Pancreatic Islet Cell Proliferation

Abstract: BackgroundIslet 1 (ISL1), a LIM-homeodomain transcription factor is essential for promoting pancreatic islets proliferation and maintaining endocrine cells survival in embryonic and postnatal pancreatic islets. However, how ISL1 exerts the role in adult islets is, to date, not clear.Methodology/Principal FindingsOur results show that ISL1 expression was up-regulated at the mRNA level both in cultured pancreatic cells undergoing glucose oxidase stimulation as well in type 1 and type 2 diabetes mouse models. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 28 publications
1
69
3
1
Order By: Relevance
“…Alternatively, these genes might be direct targets of additional transcriptional regulator(s) yet to be identified using PCR-based transcription factor screens or RNA-Seq. 32 Furthermore, while Guo and colleagues had reported that Isl-1 can promote cell proliferation and attenuate cell death against oxidative stress in isolated rat islets and HIT-T15 cells, 16 we did not detect significant changes in cell proliferation or cell survival in our transgenic mouse model. The discrepancy between these findings might simply due to the high levels of Isl-1 expression achieved in the lentivirus-based in vitro model, which might lead to activation of different gene programs.…”
Section: 31contrasting
confidence: 53%
See 2 more Smart Citations
“…Alternatively, these genes might be direct targets of additional transcriptional regulator(s) yet to be identified using PCR-based transcription factor screens or RNA-Seq. 32 Furthermore, while Guo and colleagues had reported that Isl-1 can promote cell proliferation and attenuate cell death against oxidative stress in isolated rat islets and HIT-T15 cells, 16 we did not detect significant changes in cell proliferation or cell survival in our transgenic mouse model. The discrepancy between these findings might simply due to the high levels of Isl-1 expression achieved in the lentivirus-based in vitro model, which might lead to activation of different gene programs.…”
Section: 31contrasting
confidence: 53%
“…The discrepancy between these findings might simply due to the high levels of Isl-1 expression achieved in the lentivirus-based in vitro model, which might lead to activation of different gene programs. 16 In conclusion, these novel findings provide the islet biology community with the gene expression profile of enhanced β-cell function. Future experiments designed to manipulate these genes in mouse models or cell cultures will lead to better understanding of how insulin secretion is regulated and how glucose homeostasis is maintained in adult animals.…”
Section: 31mentioning
confidence: 82%
See 1 more Smart Citation
“…In the pancreas, where ISL1 is expressed in the normal islet cells, it is known to represent a differentiation marker. [4][5][6][7][8] Thus, expression of ISL1 in pancreatic NETs most likely reflects the high differentiation status of these neoplasms. 10,11 Accordingly, it is not surprising that ISL1 is lacking or only weakly expressed in poorly differentiated pancreatic neuroendocrine carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…3 ISL1 has an important role in the embryogenesis and differentiation of the insulinproducing pancreatic beta cells within the islets of Langerhans. [4][5][6][7] Deficiency of ISL1 was associated with absence of neural tube motor neuron differentiation in mouse experiments. 8 Apart from its role in the cell line development of the endocrine pancreas, ISL1 was found to have a major role as a marker of cardiac progenitor cell lineage.…”
mentioning
confidence: 94%